Pharmacist-led Intervention in Treatment Non-adherence and Associated Direct Costs of Management Among Ambulatory Patients With Type 2 Diabetes in Southwestern Nigeria (2021)
Background: Non-adherence to recommended therapy remains a challenge to achieving optimal clinical outcome with resultant economic implications. Objective: To evaluate the effect of a pharmacist-led intervention on treatment non-adherence and direct costs of management among patients with type 2 diabetes (T2D). Method: A quasi-experimental study among 201-patients with T2D recruited from two-tertiary healthcare facilities in southwestern Nigeria using semi-structured interview. Patients were assigned into control (HbA1c < 7%, n = 95) and intervention (HbA1c ≥ 7%, n = 106) groups. Baseline questionnaire comprised modified 4-item Medication Adherence Questions (MAQ), Perceived Dietary Adherence Questionnaire (PDAQ) and International Physical Activity Questionnaire, to assess participants’ adherence to medications, diet and physical activity, respectively. Postbaseline, participants were followed-up for 6-month with patient-specific educational intervention provided to resolve adherence discrepancies in the intervention group only, while control group continued to receive usual care. Subsequently, direct costs of management for 6-month pre-baseline and 6-month post-baseline were estimated for both groups. Data were summarized using descriptive statistics. Chi-square, McNemar and paired t-test were used to evaluate categorical and continuous variables at p < 0.05